2017
DOI: 10.5811/westjem.2016.10.31492
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Top-cited Articles in Emergency Medicine Education Literature

Abstract: IntroductionDissemination of educational research is critical to improving medical education, promotion of faculty and ultimately patient care. The objective of this study was to identify the top 25 cited education articles in the emergency medicine (EM) literature and the top 25 cited EM education articles in all journals, as well as report on the characteristics of the articles.MethodsTwo searches were conducted in the Web of Science in June 2016 using a list of education-related search terms. We searched 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Selected articles were published in a variety of surgical journals and originated from several different countries. The seminal articles for each procedure are reported on Tables 1,2,3,4,5,6,7,8. (2014) Single-stage laparoscopic common bile duct exploration and cholecystectomy versus two-stage endoscopic stone extraction followed by laparoscopic cholecystectomy for patients with concomitant gallbladder stones and common bile duct stones: a randomized controlled trial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selected articles were published in a variety of surgical journals and originated from several different countries. The seminal articles for each procedure are reported on Tables 1,2,3,4,5,6,7,8. (2014) Single-stage laparoscopic common bile duct exploration and cholecystectomy versus two-stage endoscopic stone extraction followed by laparoscopic cholecystectomy for patients with concomitant gallbladder stones and common bile duct stones: a randomized controlled trial.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have identified the top-cited articles in urology, [4] orthopedic surgery [5], arthroscopy, [6] emergency medicine, [7] plastic surgery, [8] and medical education [3]. Nevertheless, we could not identify publications relevant to seminal papers in general surgery and the anchoring procedures of the SAGES Masters program, which is why we undertook this project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the second-most cited article in emergency medicine education literature ‘Achieving Quality in Clinical Decision Making: Cognitive Strategies & Detection of Bias’ from Croskerry and colleagues,15 the following strategies could have been used to avoid cognitive bias: raising awareness of the anchoring tendency (anchoring bias), staying alert for discriminatory comments about patients that may lead to unjustified expectations (ascertainment bias), raising awareness of the framing tendency and its pitfalls (framing effect) and being be aware of the tendency to pay too much attention to the most readily available information (availability bias). Using a form of ‘debiasing’, the authors hope not only to show some typical errors but also emphasise ways how to avoid it.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the overall impact factor of medical education publications has also been increasing over time, which is likely due to a combination of greater number of publications and higher‐quality research . EM education researchers are increasingly publishing in both EM and non‐EM journals . This has resulted in increasing application of methods that are more common in other fields, such as the social sciences.…”
Section: Advances In Medical Education Scholarshipmentioning
confidence: 99%